Altered monocyte and NK cell phenotypes correlate with posttrauma infection. Issue 2 (August 2019) - Seshadri, Anupamaa; Brat, Gabriel A.; Yorkgitis, Brian K.; Giangola, Matt; Keegan, Joshua; Nguyen, Jennifer P.; Li, Wei; Nakahori, Yasutaka; Wada, Takeshi; Hauser, Carl; Salim, Ali; Askari, Reza; et al.
Abstract : BACKGROUND: Trauma induces a complex immune response, requiring a systems biology approach to capture multicellular changes. Using mass cytometry by time-of-flight (CyTOF), we evaluated time-dependent changes in peripheral blood in trauma patients to identify changes correlated with infection. METHODS: Total leukocytes were prepared via red blood cell lysis using peripheral blood samples from trauma patients with an Injury Severity Score greater than 20 at Days 1, 3, and 5 after injury, and from age- and sex-matched uninjured controls. Cells were stained using a 33-marker immunophenotyping CyTOF panel. Statistics were calculated using one-way analysis of variance with multiple comparisons. RESULTS: The CyTOF staining demonstrated changes in many cell subsets. The mean expression intensity of CD86 on monocytes decreased significantly at all time points after injury. When the patients were stratified based on development of infection, there was a trend to decreased CD86 expression on monocytes of those patients that developed subsequent infection. Based on stratification, we identified significantly increased expression of CD39 on NK cells only in patients that developed an infection. CONCLUSION: This study used a systems biology approach to identify novel changes in circulating immune cell subsets in trauma patients correlating with post-traumatic infection. Decreased expression of CD86, a costimulatory molecule, on monocytes demonstrates that trauma affects the innate system's ability to control T-cell immunity. We also found that CD39 expression on NK cells increased significantly in patients with subsequent infection. CD39 is a protein that generates adenosine, which has immunosuppressive effects on several immune cell types including NK cells. In summary, our results point to pathways that may be central to second-hit infections and further study to delineate these pathways could be key to generating clinical biomarkers or targeted immune therapies for trauma patients. LEVEL OF EVIDENCE: Prognostic study, level II. Abstract : Supplemental digital content is available in the text.